The role of the Education Quality and Accountability Unit in developing the administrative competencies of school principals in Kasbah Irbid District from the point of view of its teachers - Sayeb, Na’imeh Kbeah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the role of the Education Quality and Accountability Unit in developing the administrative competencies of the principals of Kasbah Irbid District schools from the point of view of its teachers. (291) a male and female teacher; In government schools affiliated to the Directorate of Education in the Kasbah of Irbid district in Jordan, the results of the study showed that the responses of the study sample members about the role of the Education Quality and Accountability Unit in developing the administrative competencies of the school principals of the Kasbah of Irbid district from the point of view of their teachers came with an arithmetic average (3.31), with a degree (medium).). The results also showed that there were no statistically significant differences at the significance level (α≤0.05) due to the effect of a variable (gender, years of experience). While it was found that there were statistically significant differences at the significance level (α≤0.05) due to the effect of the educational qualification variable. In light of the results, the researcher recommended setting specific criteria for applying educational accountability; School principals adopt an administrative philosophy and organizational methods that support the participation of employees in the planning and implementation of school programs, which increases the effectiveness of organizational development and managerial competencies.